The DYD Stakeholder Consultation Process : A User Guide. - Dowling, David; Hadgraft, Roger (Office for Learning and Teaching, 2013)
User guide produced as part of a project that developed an efficient, effective and inclusive consultation process, the DYD process, which may be used by discipline stakeholders to define practitioner-authenticated graduate outcomes for their discipline. The guide was prepared to enable education institutions and industry organisations to use the Define Your Discipline (DYD) Stakeholder Consultation Process to develop practitioner-authenticated Graduate Capability Frameworks for the programs in their discipline. The Graduate Capability Framework can then be used to guide the development of curriculum for a program, to inform a review of existing curriculum, or to guide reviews by external accrediting organisations.